Assessment of a Treatment Planning Protocol for the Reduction of Dosimetry Calculation Errors in Radiotherapy for Head and Neck Patients with Dental Implants - Emberru, Moesha (My University, 2021)
Concerns arise in radiation therapy for head and neck cancers when dental prostheses are involved. These prostheses are high-density materials that induce image artifacts in computed tomography (CT) scans used for dose calculation. Two approaches are utilized in mitigating the impact of these artifacts on the accuracy of dose calculation. First, metal artifact reduction (MAR) algorithms or dual-energy CT scans are used to recover image quality. Second, a planning protocol is adopted whereby residual artifacts are manually contoured and assigned appropriate densities. This study evaluated the current planning process using a holistic approach. In this work, an axial section of a head phantom containing dental implants at the level of the oral cavity was constructed and scanned using various protocols on two different commercial scanners; Philips and Siemens, to assess the appearance of artifacts. An MVCT image set was merged with the corresponding kVCT image to improve visualization of the dental implants for use in density overrides. Three ion chamber measurement points in the simulated mouth facilitated the determination of measured dose which was compared to calculated dose at various single beam irradiation geometries. The influence of density override values on agreement between calculation and measurement was investigated for each geometry and imaging modality. Percent error was computed, and initial results compared to results manipulated by use of; a CT density table (Head); density overrides of walls and wax; and density overrides of walls, wax, and effective density of saturation regions. The study established that normal tissue doses are not significantly affected by metal artifact reduction (MAR) algorithms, and improvements in dose calculation compared to uncorrected CT images are small. Furthermore, the inclusion of a MVCT image set improved implant visualization reducing the treatment planning time while providing more information. Evidence led to the deduction that manual overrides of effective density for clipped OMAR CT pixels reduce dose calculation errors. When the phantom was configured with amalgam and Co-Cr-Mo alloy dental implants the effective density of these implants was found to be 4.5 g/cm3. When the phantom was configured with implants containing amalgam and gold, the effective density of amalgam in the presence of gold was 5.5 g/cm3 while gold had an effective density of 6.5 g/cm3. The median and maximum range of errors for the uncorrected images were ± 0.6 % and 7.4% respectively for the phantom configured with amalgam and Co-Cr-Mo (tray one) and ± 0.5 % and 18.1 % respectively for the phantom containing amalgam and gold (tray two). The median and maximum range of errors for the corrected images after applying overrides of effective densities were ± 0.5 % and 4.7% respectively for tray one and ± 0.3 % and 7.7 % respectively for tray two. In conclusion, introduction of density overrides of walls, wax and effective density of high-density materials can reduce the errors induced by metal artifacts and improve the accuracy of dose calculations in treatment planning systems to deliver the relevant dose to a target organ.
Keywords: Metal Artifact Reduction; Amalgam; CT; Dose calculation